Pengaruh Etika Kerja, Budaya Organisasi Dan Beban Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening - Nurhasanah Nurhasanah; Jufrizen Jufrizen; Zulaspan Tupti (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The study aims to analyze the influence of work ethic, organizational culture and workload on employee performance, analyze the effect of job satisfaction on employee performance and to analyze whether job satisfaction is a mediation variable between work ethic, organizational culture and workload on performance at PT. Perkebunan Nusantara IV (Persero) Dolok Sinumbah. The research method used in this study is Descriptive Of Cwantitative. The population of the study was 81 samples or 81 employees. The method of data collection is done using a questionnaire. Data analysis techniques using PLS-SEM. The results showed that directly, work ethic has a positive and significant effect on job satisfaction, organizational culture has a positive and significant effect on job satisfaction, workload has a positive and significant effect on job satisfaction, work ethic has a positive and significant effect on performance, organizational culture has a positive and significant effect on performance, workload has a positive and significant effect on performance, job satisfaction has a positive and significant effect on performance. Indirectly job satisfaction mediate the relationship between work ethic variables and performance variables. Indirectly job satisfaction also mediate the relationship between organizational culture variables and performance variables and the last is that indirectly job satisfaction mediate the relationship between workload variables and performance variables.